2013
DOI: 10.3389/fnhum.2013.00168
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Noise: Using Temporal ICA to Extract Meaningful Information from High-Frequency fMRI Signal Fluctuations during Rest

Abstract: Analysis of resting-state networks using fMRI usually ignores high-frequency fluctuations in the BOLD signal – be it because of low TR prohibiting the analysis of fluctuations with frequencies higher than 0.25 Hz (for a typical TR of 2 s), or because of the application of a bandpass filter (commonly restricting the signal to frequencies lower than 0.1 Hz). While the standard model of convolving neuronal activity with a hemodynamic response function suggests that the signal of interest in fMRI is characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
143
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 48 publications
(59 reference statements)
3
143
0
Order By: Relevance
“…Using similar acquisition methods, Lee et al (2012) have demonstrated interhemispheric connectivity in the sensory motor cortex from BOLD fluctuations in higher frequency ranges ( > 0.25 Hz) than traditionally used in resting-state fMRI studies (0.01-0.1 Hz). Similarly, Boubela et al (2013) have shown the presence of the default mode and frontal-parietal networks by applying ICA to BOLD fMRI data acquired at higher sampling rate (TR = 354 msec, sampling frequency = 2.82 Hz).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Using similar acquisition methods, Lee et al (2012) have demonstrated interhemispheric connectivity in the sensory motor cortex from BOLD fluctuations in higher frequency ranges ( > 0.25 Hz) than traditionally used in resting-state fMRI studies (0.01-0.1 Hz). Similarly, Boubela et al (2013) have shown the presence of the default mode and frontal-parietal networks by applying ICA to BOLD fMRI data acquired at higher sampling rate (TR = 354 msec, sampling frequency = 2.82 Hz).…”
Section: Introductionmentioning
confidence: 91%
“…Although earlier studies have described the presence of different RSNs in higher frequency bands than LFFs ( > 0.1 Hz), these studies were mainly performed using a single approach to study RSNs (Boubela et al, 2013;Lee et al, 2012). Moreover, these reports focused on specific networks rather than on the entire collection of RSNs (Boubela et al, 2013;Lee et al, 2012;Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the fact that fMRI temporal resolution is limited by slow neurovascular coupling has restricted the majority of fMRI studies to studying dynamics in the <0.1-Hz range, because periodic oscillations above that frequency range are expected to be vanishingly small. Despite this evidence, recent studies performed during the resting state have suggested that there are significant neuronally driven blood oxygenation level-dependent (BOLD) contributions to fMRI signals at frequencies above 0.1 Hz (24)(25)(26)(27). However, a challenge in interpreting fMRI oscillatory dynamics measured during the resting state is that the underlying brain activity is not known.…”
mentioning
confidence: 99%
“…These novel developments help to cover a wide range of spatio-temporal resolution and sensitivity (Figure 1; adopted from Meikle et al, 2005), complementing each other in both parameters displayed, as well as energy levels (SAR) to be applied. Another important parameter would be the temporal resolution, in particular relative to physiological motion, to help increase functional contrast-to-noise ratio by specifically reducing physiological noise (Boubela et al, 2013). Otherwise, group averaging may be rather limited to extract more subtle functional differences (Biswal et al, 2010;Kalcher et al, 2012), at least in functional MRI.…”
mentioning
confidence: 99%